2021
DOI: 10.3389/fonc.2021.682998
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomic Analysis of Papillary Thyroid Carcinoma for Prediction of Cervical Lymph Node Metastasis: A Preliminary Study

Abstract: BackgroundPapillary thyroid carcinoma (PTC) is characterized by frequent metastases to cervical lymph nodes (CLNs), and the presence of lymph node metastasis at diagnosis has a significant impact on the surgical approach. Therefore, we established a radiomic signature to predict the CLN status of PTC patients using preoperative thyroid ultrasound, and investigated the association between the radiomic features and underlying molecular characteristics of PTC tumors.MethodsIn total, 270 patients were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…The AUCs of the three models were 0.833, 0.731, and 0.711, respectively, which demonstrated that both the thyroid gland and thyroid nodules contributed to the identification of CLNM. This result was supported by Tong et al, who reported that the radiomics features of thyroid nodules can predict CLNM in patients with PTC (28). However, only a small number of patients with HT were included in this study.…”
Section: Discussionsupporting
confidence: 67%
“…The AUCs of the three models were 0.833, 0.731, and 0.711, respectively, which demonstrated that both the thyroid gland and thyroid nodules contributed to the identification of CLNM. This result was supported by Tong et al, who reported that the radiomics features of thyroid nodules can predict CLNM in patients with PTC (28). However, only a small number of patients with HT were included in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Besides, US examination is an empirical diagnosis which is greatly affected by the expertise of the operator; therefore, prone to interobserver variability when determining lateral LNM [ 8 ]. Many studies have investigated the association between cervical LNM and the morphologic US features of the primary tumor, and have reported that the “taller than wide” shape, tumor size, presence of calcification, and closer distance between tumor and capsule were independent risk factors for LNM [ 15 , 24 26 ]. Although the US features mentioned above are encouraging, the imaging features are also based on the judgment of the performing physician and thus, lack objectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided microwave ablation (MWA) technology has achieved good safety and therapeutic effects in the treatment of benign thyroid nodules, and compared to OS, MWA technology results in fewer postoperative complications, has no effect on thyroid function, causes less trauma, and enables the faster recovery, and improved appearance of some PTMC patients (7)(8)(9). However, Tong's study mentioned that MWA only inactivates cancer nodules and does not remove the surrounding lymph nodes, and has a high risk of residual cancer foci and lymph node metastasis, even after microwave ablation, there are still a few tumors with recurrence and lymph node metastasis, which can not be used as a routine treatment for primary operable primary thyroid cancer (10). Therefore, MWA is a non-radical treatment for tumors, and its use as a routine treatment remains controversial (11).…”
Section: Introductionmentioning
confidence: 99%